Bank Failures and Fiscal Austerity : Policy Presecriptions for a Developing Country - Feltenstein, Andrew (IMF Working Papers; Working Paper ;, 2000)
This work employs a dynamic general equilibrium model to evaluate the causes and implications of bank insolvencies. The model is applied to stylized data from several South Asian countries. It derives conclusions about policy instruments designed to alleviate the impact of insolvencies. Firms are subject to intertemporal solvency conditions, and the public withdraws deposits when borrowers default. If banks optimize by restricting credit to risky borrowers, these failures can be partially avoided. Numerical simulations conclude that the combination of compensating monetary policy and restrictive fiscal policy offers the best way of responding to a bank crisis caused by exogenous shocks.